The role of spirituality in facilitating personal development according to the Pauline corpus - Beer, Frederick J. de; Rand, Jan A. du (In die Skriflig/In Luce Verbi, 2021)
The concept of personal growth and development has been an ever-growing discipline in the last couple of decades, especially encapsulated by self-help constructs. The market for self-improvement literature, also known as self-help literature, is one of the fastest-growing fields over the last two decades. Spirituality has also become a prominent element in these popular self-help literatures. Interest in spirituality as a scholarly discipline, guided by academic disciplines, has grown in the last few decades, but so too has the interest in spirituality as a prominent component in popular texts such as self-help literature. Bible citations and concepts are frequently included in the theories on spirituality in these popular literature, but are not always interpreted within Christian constructs. The tendency to use Bible citations and concepts created the impression that spirituality in these self-help theories is a Christian precept. Spirituality, as a key factor in self-help literature, was examined in view of Christian Spirituality and biblical concepts. Transformation, experience, the body and the mind are central aspects of the spirituality advocated by these self-help literature. These central aspects were evaluated from a Pauline perspective and in view of Christian Spirituality with specific reference to Romans 8:1–30 and Romans 12:1–2. The specific reference to the Pauline corpus was motivated by the hypothesis that Christianity can historically claim intellectual property to the word spirituality , as the origins of the word can be attributed to Paul. Spirituality, in the quest for personal growth and development, implies the work of the Spirit in the life of the believer as a result of the Christ event. Christian Spirituality underlines the personal experience of the Spirit as evinced in the Pauline corpus. While spirituality is a scholarly discipline guided by academic disciplines, spirituality is also a key construct in popular self-help literature. The spirituality suggested in these self-help literature does not necessarily accord with biblical constructs. In Christian Spirituality, transformation is the consequence of the presence of the Spirit and not only by the mere implementation of so-called self-help methodologies or undefined spirituality. Contribution: This article will assist the Christian believer who, in the quest for personal growth and development, engages spirituality with a biblical construct from a Pauline perspective and understanding of the role and work of the Spirit. While being aware of the fact that spirituality cannot be defined in restrictive terms, this article will nevertheless present some understanding of Christian Spirituality and the necessity of the Spirit as it relates to personal growth and development.
free